If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4ln(4x + -1) = 12 Reorder the terms: 4ln(-1 + 4x) = 12 (-1 * 4ln + 4x * 4ln) = 12 (-4ln + 16lnx) = 12 Solving -4ln + 16lnx = 12 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -12 + -4ln + 16lnx = 12 + -12 Combine like terms: 12 + -12 = 0 -12 + -4ln + 16lnx = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-3 + -1ln + 4lnx) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-3 + -1ln + 4lnx)' equal to zero and attempt to solve: Simplifying -3 + -1ln + 4lnx = 0 Solving -3 + -1ln + 4lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -1ln + 3 + 4lnx = 0 + 3 Reorder the terms: -3 + 3 + -1ln + 4lnx = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1ln + 4lnx = 0 + 3 -1ln + 4lnx = 0 + 3 Combine like terms: 0 + 3 = 3 -1ln + 4lnx = 3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (x+1+4i)(x-1+4i)= | | 7.25t+8=13.5t+13 | | Y-0.8y=100+125+125-30 | | X^2=1y | | Y-0.8y=0.2y | | 4x+54=7x+9 | | 0=7c-(81+4c) | | (7-5)5/4 | | Ln(1-2y)=t | | In(3x-2)+in(x-1)=2inx | | -2(2x-3)=32 | | 3u-14=40 | | -32=-35-5n^2 | | 6=2v-16 | | 5x-2=7(2x-8) | | 2y-15=19 | | 7n^2-11n=-4 | | 9+16-9(1)2= | | r^2-4r-15=-3 | | x/9=1/6 | | 3lnx-lny=0 | | (Y-18)/6=0.7 | | -3(-5-b)=.33(b+13) | | (Y-18)/6 | | 12+8k=84 | | Y-18/6 | | 0.6(t+36)=-3(4-t) | | 19x+(-9)=-29+14x | | 12b+12b=3 | | 5/8x40 | | 9-w=215 | | 1/3.(180-×) |